Common patient‐reported sources of cancer‐related distress in adults with cancer: A systematic review - Jennifer M. Stevens; Kathleen Montgomery; Megan Miller; Seyedehtanaz Saeidzadeh; Kristine L. Kwekkeboom (Cancer Medicine, 2024)
Abstract Background Cancer‐related distress (CRD) is widely experienced by people with cancer and is associated with poor outcomes. CRD screening is a recommended practice; however, CRD remains under‐treated due to limited resources targeting unique sources (problems) contributing to CRD. Understanding which sources of CRD are most commonly reported will allow allocation of resources including equipping healthcare providers for intervention. Methods We conducted a systematic review to describe the frequency of patient‐reported sources of CRD and to identify relationships with CRD severity, demographics, and clinical characteristics. We included empirical studies that screened adults with cancer using the NCCN or similar problem list. Most and least common sources of CRD were identified using weighted proportions computed across studies. Relationships between sources of CRD and CRD severity, demographics, and clinical characteristics were summarized narratively. Results Forty‐eight studies were included. The most frequent sources of CRD were worry (55%), fatigue (54%), fears (45%), sadness (44%), pain (41%), and sleep disturbance (40%). Having enough food (0%), substance abuse (3%), childbearing ability (5%), fevers (5%), and spiritual concerns (5%) were infrequently reported. Sources of CRD were related to CRD severity, sex, age, race, marital status, income, education, rurality, treatment type, cancer grade, performance status, and timing of screening. Conclusions Sources of CRD were most frequently emotional and physical, and resources should be targeted to these sources. Relationships between sources of CRD and demographic and clinical variables may suggest profiles of patient subgroups that share similar sources of CRD. Further investigation is necessary to direct intervention development and testing.